Pengaruh Motivasi dan Pengetahuan Kewirausahaan terhadap Minat Berwirausaha pada Mahasiswa STIT Payakumbuh - Sonita Yulianti; Dina Istiqomah (ARZUSIN, 2025)
The high unemployment rate in Indonesia necessitates that university students not rely solely on formal employment opportunities but also develop the ability to create opportunities through entrepreneurial activities. However, observations at STIT Payakumbuh reveal that many students exhibit low entrepreneurial interest, influenced by perceptions that entrepreneurship requires substantial capital, involves high risk, and demands strong self-confidence—qualities they believe they lack. This study aims to analyze the influence of motivation and entrepreneurial knowledge on students’ entrepreneurial interest at STIT Payakumbuh. A quantitative field research approach was adopted, involving a questionnaire distributed to 30 respondents selected using probability sampling. Data analysis included validity and reliability tests, classical assumption testing, t-tests, F-tests, and the coefficient of determination, processed using SPSS 24. The results indicate that motivation has a significant effect on students’ entrepreneurial interest, and entrepreneurial knowledge also contributes positively in a partial capacity. Simultaneously, both variables significantly influence entrepreneurial interest, with a combined contribution of 60.8%. These findings underscore the importance of strengthening internal motivation and enhancing entrepreneurial literacy to foster student readiness and a proactive mindset toward independent business ventures.